Utilizamos diferentes formas para medir - Gomez Ramirez, Jessica Lisbeth (2018)
Through this leraning session development, it is intended to build in the student the necessary information so that they learn how to carry out measurements and comparisons objects lengths in their environment, with arbitrary units. Learning mathematics contributes to forming citizens capable of searching, organizing, systematizing and analyzing information to understand and interpret their surrounding world, to solve problems using mathematical strategies and knowledge. The magnitudes measurement constitutes a contents traditionally list used in elementary and high school education, no curriculum reform has left out this thematic nucleus of great utility in practical citizen life. But it is that, in addition to this utility, if it is analyzed from a mathematical point of view, what knowledge is behind the magnitudes measurement, we find refined and complex concepts that have been incorporated into higher mathematics very recently. We are obviously referring to the measurement theory, great importance in mathematics.